Nagapattinam to Suvarnadwipa : reflections on the Chola naval expeditions to Southeast Asia (Institute of Southeast Asian Studies, 2001)
This is the Tamil version of Nagapattinam to Suvarnadwipa, Reflections on the Chola Naval Expeditions to Southeast Asia, published by ISEAS in 2009. The expansion of the Cholas from their base in the Kaveri Delta saw this growing power subdue the kingdoms of southern India, as well as occupy Sri Lanka and the Maldives, by the early eleventh century. It was also during this period that the Cholas initiated links with Song China.Concurrently, the Southeast Asian polity of Sriwijaya had, through its Sumatran and Malayan ports, come to occupy a key position in East-West maritime trade, requiring engagement with both Song China to the north and the Chola kingdom to its west.
Cover, Title,Nagapattinam to Suvarnadwipa : reflections on the Chola naval expeditions to Southeast Asia--Preface, Introduction, TOC,Table of Contents--References, Appendix, Index,Appendix I.--References, Appendix, Index,Appendix II.--References, Appendix, Index,Index.
Keywords: Chola dynasty, 850-1279--Congresses; India--Relations--Southeast Asia--Congresses; Southeast Asia--Relations--India--Congresses; Asia--Commerce--History--Congresses